Training Report in Safe Alternate Wetting and Drying Irrigation Method for Rice Cultivation with Less Water Use - Dossou-Yovo, Elliott Ronald; Tchetan, Blaise; Guindo, Jonathan; Koné, Pierre (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Management practices that simultaneously enhance rice yield, water productivity, labor productivity, and grain quality are needed for improving crop production and mitigating the negative impact of water scarcity on food security. Among the water-saving technologies that were developed in recent decades, the alternate wetting and drying (AWD) method of irrigation is widely advocated for its potential to increase water productivity while maintaining rice yield compared to continuous flooding. Under AWD, ﬁelds are subjected to intermittent ﬂooding where irrigation is interrupted, and water is allowed to subside until the water table falls down to a threshold below the soil surface, after which the field is re-flooded. Previous studies indicated an increase in water productivity under AWD compared to continuous flooding with other co-benefits including a decrease in methane emissions, a decrease in the concentration of arsenic in grains, and an increase in the internal phosphorus use efficiency. However, yield reductions were also reported under AWD particularly when the drying phase occurs during the flowering stage, or water recedes below 15 cm soil depth. The safe AWD was developed to ensure similar or higher rice yield and grain quality under safe AWD compared to continuous flooding. Despite the benefits of safe AWD, the technology is new, and not known by many stakeholders in Mali. AICCRA-Mali strengthened the capacity of 18 staff from Niger Office including 6 women in the implementation of safe AWD for producing rice with less water and less greenhouse gas emissions while maintaining rice yield and grain quality compared to the farmers’ practices of continuous flooding.